Crop plants yield and development following soil and foliar application of rare earths - Ribeiro, Paula Godinho (2018)
Rare earth elements (REE) are transition metals of similar physicochemical compositions that are present in phosphate rocks and their by-products, such as phosphate fertilizers. Positive effects have been reported for the agricultural application of REE, as a stimulus of photosynthesis and yield increases. Although the number of studies regarding the application of REE in plants has been increasing, our knowledge on the effect of REE applications via phosphate fertilizers is scarce. In addition, the use of REE foliar fertilizers is novel in Brazil. Field experiments were conducted in Rio Verde – GO and Lambari – MG, Brazil, aiming to: 1) evaluate the response of soybean (Glycine max L.) and common bean (Phaseolus vulgaris L.) to increasing rates of soil-applied phosphate fertilizers containing different concentrations of REE; and, 2) evaluate the effects of foliar applications of REE in the production, nutrient and protein contents of soybean and maize grains (Zea mays L.) and oil content of soybean grains. The soil experiment followed a full factorial design with two factors (4 fertilizers, 4 doses), and four blocks totaling 64 plots. The fertilizers used were: pure ammonium phosphate, without REE; single superphosphate (SSP), with low REE content; SSP from Catalão with a high content of REE and SPP from Araxá with an intermediate REE content. The P2O5 doses tested were 0, 40, 80, and 160 kg ha -1 . For the foliar application, the source used was a REE mix created from a chinese fertilizer called ―Changle‖, which is composed of 23.95% La, 41.38% Ce, 4.32% Pr, and 13.58% Nd at the following doses: 0; 0.1; 0.25; 0.5; 0.75; 1.0 kg of mix ha -1 . Nutrient analyses, yield, and grain quality were carried out at the end of the experiments. There was no effect of foliar application of REE on yield and grain quality of soybean and maize. On the other hand, in the soil experiment, the Catalão SSP consistently increased the common bean yield by about 30% over the control with pure P salt. Araxá SSP also increased the yield by about 30% when applied at a P2O5 rate of 160 kg ha -1 . For soybean, the SSP from Catalão, with 160 kg of P2O5 ha -1 , was superior to the pure salt (at the same level of P 2O5 ) and to the treatment without the addition of P. Therefore, the REE contained in these P fertilizers increased its potential to promote legume crops yield.